2020
DOI: 10.21203/rs.2.22941/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultrasound-guided Erector Spinae Plane Block for postoperative analgesia: A Meta-Analysis of Randomized Controlled Trials

Abstract: Background Ultrasound-guided Erector Spinae Plane Block (ESPB) has been increasingly applied in patients for postoperative analgesia. Its safety and effectiveness remain uncertain. This meta-analysis aimed to determine the clinical safety and efficacy of ultrasound-guided ESPB in adults undergoing general anesthesia (GA) surgeries. Methods A systematic databases search was conducted in PubMed, Embase, and the Cochrane Library for randomized controlled trials (RCTs) comparing ESPB with control or placebo. Prima… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…The important finding of the current report is that ESPB reduced postoperative opioid consumption. This concurs well with the results of previous meta-analyses [ 6 , 7 , 26 ]. Opioid has long been used as a means to manage acute postoperative and postprocedural pain; however, a recent study reviewing clinical and administrative data from 135,379 adult patients receiving opioids after hospital-based surgeries or endoscopic procedures reported that 10.6% of the patients experienced opioid-related adverse events, which were related to poor outcomes, including increased inpatient mortality, prolonged length of hospital stay, and higher 30-day readmission rates [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The important finding of the current report is that ESPB reduced postoperative opioid consumption. This concurs well with the results of previous meta-analyses [ 6 , 7 , 26 ]. Opioid has long been used as a means to manage acute postoperative and postprocedural pain; however, a recent study reviewing clinical and administrative data from 135,379 adult patients receiving opioids after hospital-based surgeries or endoscopic procedures reported that 10.6% of the patients experienced opioid-related adverse events, which were related to poor outcomes, including increased inpatient mortality, prolonged length of hospital stay, and higher 30-day readmission rates [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the past year, publications referring to ESPB have increased significantly. Subsequently, meta-analyses have been published, supporting the analgesic efficacy of ESPB [ 6 , 7 ]. However, previous meta-analyses included various types of surgery, ranging from laparoscopic procedures to cardiothoracic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…ESPB, a new regional anesthesia technique reported for the first time in 2016 [5], is attracting the attention of clinical practitioners because of its ease of delivery and relative safety. Several systematic reviews and metaanalyses have been conducted to evaluate ESPB in surgery; however, they were limited to other types of surgery, including breast and thoracic surgeries [25,26] or a combination of spinal surgery and multiple surgical procedures [27], with very few studies of spinal surgery being included. To the best of our knowledge, this is the first systematic review and meta-analysis that assessed the effectiveness of ESPB in spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There are indeed previous reports that address this subject and these have been reviewed. 15 Attempts have been made to conduct meta-analyses of trials that investigate the efficacy of erector spinae 16,17 and serratus anterior blocks 18,19 compared with systemic analgesia alone but these are largely inconclusive because the evidence is weak from small, low-quality heterogenous studies. At best, it would appear that erector spinae and serratus anterior blocks provide statistically significant but clinically unimportant changes compared with systemic analgesia alone [16][17][18][19] .…”
Section: Takedownmentioning
confidence: 99%
“…15 Attempts have been made to conduct meta-analyses of trials that investigate the efficacy of erector spinae 16,17 and serratus anterior blocks 18,19 compared with systemic analgesia alone but these are largely inconclusive because the evidence is weak from small, low-quality heterogenous studies. At best, it would appear that erector spinae and serratus anterior blocks provide statistically significant but clinically unimportant changes compared with systemic analgesia alone [16][17][18][19] . We would argue that new techniques should be compared with the current gold standard, which in the case of analgesia for thoracic surgery is thoracic epidural or paravertebral analgesia.…”
Section: Takedownmentioning
confidence: 99%